WSTĘPNE UWAGI NA TEMAT AKCENTUACJI W POLSKIEJ GWARZE MIESZKAŃCÓW WSI WIERSZYNA NA SYBERII - Paśko-Koneczniak, Dorota (Przegląd Rusycystyczny, 2018)
PRELIMINARY REMARKS ON STRESS PATTERNS IN THE POLISH DIALECT USED BY THE INHABITANTS OF VERSHINA, A VILLAGE IN SIBERIA Summary The aim of the article is to present and analyse the stress patterns of borrowings present in the Polish dialect used by the inhabitants of Vershina, which is a village situated about 140 kilometres north of Irkutsk. The village is inhabited by the descendants of voluntary settlers from Poland. They form a bilingual community and use both Russian and Polish depending on the communicative context. The lexical scope of the dialect is influenced by borrowings from Russian, especially as regards every-day expressions. Borrowed lexemes are assimilated in terms of word stress, phonetic and morphological aspects, and word formation.